An exploratory study of students’ perceptions of advice and support services in a science university - Althewini, Abdulaziz Mohammed (Frontiers in Medicine, 2025)
This exploratory qualitative study investigates the experiences of health sciences students with academic advising in an English as a Medium of Instruction (EMI) context. Through virtual semi-structured interviews with four students, the study identifies preliminary themes: limited accessibility of support services, the need for personalized advising, cultural and language influences, and the role of technology in academic support. Students expressed a preference for discussing complex issues in their native Arabic language, highlighting the importance of linguistic and cultural sensitivity. While AI-based advising tools improve accessibility, participants emphasized the irreplaceable value of human-centered, empathetic guidance. Given the small sample size, the findings do not claim generalizability or thematic saturation but are intended to offer early, exploratory insights that may inform future research. The study recommends blended advising models that integrate technology with personalized support and calls for culturally responsive advisor training to enhance student satisfaction and success.